A flow admission control scheme for Qos in wireless ad hoc networks - Qin, Yang (2013)
It is challenging to provide QoS in wireless ad hoc networks. One of the main problems that affects QoS in wireless ad hoc networks is the multi-hop nature of the network which generates high volume of control overhead. Such overhead is necessary to create/maintain network routes. Congested routes further aggravate the existing problem by generating more control packets for performing route maintenance. In addition, established routes are not well-protected and are subject to the changes in traffic load, which further reduces the QoS provided and wastes network resources. Therefore, in this paper, we propose a flow admission control scheme at the routing layer to mitigate the above problem by taking pre-emptive measures through bandwidth and congestion estimation. The scheme can reduce unnecessary control overhead for route maintenance and select a proper route for a flow, thus improve the overall network performance. Moreover, established routes can be protected from any changes in traffic load for the duration of the route lifetime. Our extensive simulation results demonstrate that the proposed scheme achieves good network performance.